POWER PARAMETERS OF THE PROCESS OF END FORMING OF THICK WALLED TUBES - V. A. Tamila (Литьë и металлургия, 2017)
Analysis of forces acting on the rolls in the radial direction made by the analytical method and with use of computer modeling techniques is made. Application of FEM has allowed to calculate distribution of power parameters of the technological process during time. The deviation of the experimental data on the results of analytical calculation is within 3%.